2011
DOI: 10.1097/smj.0b013e318213ec03
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tracheal Mucosa Involvement on Clinical Characteristics of Sarcoidosis

Abstract: Sarcoidosis with tracheal mucosa involvement that can lead to cough and other respiratory symptoms, may be a manifestation of sarcoidosis activity, and usually requires drug treatment (including corticosteroid treatment).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This study compared respiratory symptoms in 87 patients who had undergone tracheal biopsy and found that significantly more (92%) of those who had granulomatous tracheitis complained of cough compared with those (49%) who had normal tracheal biopsies [6]. This study did not report on the bronchoscopic appearances of the bronchial mucosa nor on the histological appearances of bronchial biopsies but it seems plausible that cough in the latter group may have been caused by inflammation of the bronchi or smaller airways without tracheal involvement.…”
Section: Sarcoidosismentioning
confidence: 99%
“…This study compared respiratory symptoms in 87 patients who had undergone tracheal biopsy and found that significantly more (92%) of those who had granulomatous tracheitis complained of cough compared with those (49%) who had normal tracheal biopsies [6]. This study did not report on the bronchoscopic appearances of the bronchial mucosa nor on the histological appearances of bronchial biopsies but it seems plausible that cough in the latter group may have been caused by inflammation of the bronchi or smaller airways without tracheal involvement.…”
Section: Sarcoidosismentioning
confidence: 99%
“…Few have investigated the mechanisms of cough in sarcoidosis to date. Postulated mechanisms include airway inflammation or hyper-responsiveness, interstitial distortion, vagus nerve disruption, laryngeal and vocal cord involvement, granulomatous infiltration of the pulmonary vasculature, and heightened CRS ( 63 , 142 ).…”
Section: Sarcoidosismentioning
confidence: 99%
“…In a retrospective study of tracheal biopsy in sarcoidosis, Ding et al . reported more self-reported cough in patients with tracheitis compared to those without (92% vs. 49% respectively) ( 63 ). Taken together, endobronchial sarcoidosis and airway neutrophilic inflammation are associated with cough though the precise mechanism remains unexplored.…”
Section: Sarcoidosismentioning
confidence: 99%
“…Probably the most common mechanisms causing pulmonary sarcoidosis-associated cough are airway irritation and mechanical airway damage caused directly by granulomatous inflammation. Sarcoid granulomas have a predilection for depositing in the airways [ 20 ] and the presence of endobronchial sarcoidosis lesions has been associated with cough [ 21 , 22 ]. This airway irritation/mechanical damage may cause an asthma-like syndrome [ 23 ] in which afferent nerve fibers are stimulated, thereby inducing cough [ 15 , 24 ].…”
Section: Coughmentioning
confidence: 99%